Marital Quality and Depression Among Women Undergoing Artificial Insemination by Donor Due to Male Irreversible Azoospermia: A 6-Year Follow-up Study in China - Shufang Wu; Linling Zhu; Shanshan Zhang; Fengyi Mo; Yali Chang; Yifei Dai; Xinyun Yang; Lanfeng Xing (Clinical and Experimental Obstetrics & Gynecology)
Background: Infertility is a stressful situation that can lead to negative emotions such as depression. In particular, women undergoing artificial insemination by donor (AID). The quality of marriage is one of the important influencing factors of infertility treatment. This study aimed to evaluate marital quality and depression among women undergoing AID due to male irreversible azoospermia. Methods: A hospital-based cohort study was conducted at Women’ s Hospital, Zhejiang University School of Medicine from July 2016 to December 2016, with a total of 128 participants enrolled. The marital quality and mental health were measured with the Dyadic Adjustment Scale (DAS) and the Self-rating Depression Scale (SDS), respectively. Results: A DAS score of ≤107, indicating poor marriage quality, was found in 40.6% of the women surveyed. These women had lower education levels and higher SDS scores. Pearson correlation coefficient and multiple regression analysis showed a significant correlation between the DAS score and factors such as the duration of marriage, education level, remarriage, and SDS score. Six years after undergoing AID, the SDS score of women remained steady (26.41 ± 4.27 at the year of AID, and 26.52 ± 6.48 for the 6-year follow-up). DAS was statistically lower at the 6-year follow-up (106.19 ± 20.17) compared to that at the AID year (114.49 ± 17.65). Unexpectedly, pregnancy was not shown to improve marital quality. Conclusions: The study’s findings suggest that women undergoing AID experience poor marital quality and exhibit high levels of depression. After a 6-year follow-up, the marital adjustment for the women worsens following AID treatment. Additionally, this trend does not appear to be influenced by whether the couple bears and raises a child conceived through AID.